Therapeutic drug monitoring in the treatment of invasive aspergillosis with voriconazole in cancer patients: an evidence-based approach - Karthaus, Meinolf; Buchheidt, Dieter (Annals of hematology, 2015)
Invasive aspergillosis (IA) is a life-threatening complication in hematological cancer patients. Voriconazole (VCZ) is the established first-line treatment of IA. VCZ has a nonlinear pharmacokinetic profile and exhibits considerable variability of drug exposure. Therefore, therapeutic drug monitoring (TDM) of VCZ may help to improve treatment results in IA patients, but evidence-based data on the clinical use of TDM in patients treated with VCZ for IA are scarce. Evidence-based guidance is needed to support decisions on the use of TDM in routine VCZ therapy of IA. Our present analysis assessed published studies for evidence-based criteria for TDM of VCZ to improve efficacy and safety of IA therapy in cancer patients. Literature searches of MEDLINE and Cochrane database were performed. We identified 27 clinical studies reporting on the use of plasma level monitoring and/or TDM for VCZ. For each study, strength of recommendation and quality of evidence were categorized according to predefined criteria. A number of studies were published on plasma level monitoring (PLM) and TDM in VCZ therapy of IA. Across studies, VCZ levels >5-5.5 mg/L were found to be associated with toxicity, while reaching minimum levels of >1-2 mg/L appeared to improve efficacy. Timing, frequency, and intervention thresholds and dosage increments of VCZ for adjustment of plasma levels remain to be established. Currently, there is still no conclusive evidence for recommendations in routine clinical practice. More data from prospective randomized studies with TDM are desirable to provide a solid evidence basis for these approaches.
Gesehen am 14.11.2017